When monoclonal antibodies are not monospecific: Hybridomas frequently express additional functional variable regions. Issue 4 (19th May 2018) - Bradbury, Andrew R. M.; Trinklein, Nathan D.; Thie, Holger; Wilkinson, Ian C.; Tandon, Atul K.; Anderson, Stephen; Bladen, Catherine L.; Jones, Brittany; Aldred, Shelley Force; Bestagno, Marco; Burrone, Oscar; Maynard, Jennifer; et al.
ABSTRACT: Monoclonal antibodies are commonly assumed to be monospecific, but anecdotal studies have reported genetic diversity in antibody heavy chain and light chain genes found within individual hybridomas. As the prevalence of such diversity has never been explored, we analyzed 185 random hybridomas, in a large multicenter dataset. The hybridomas analyzed were not biased towards those with cloning difficulties or known to have additional chains. Of the hybridomas we evaluated, 126 (68.1%) contained no additional productive chains, while the remaining 59 (31.9%) contained one or more additional productive heavy or light chains. The expression of additional chains degraded properties of the antibodies, including specificity, binding signal and/or signal-to-noise ratio, as determined by enzyme-linked immunosorbent assay and immunohistochemistry. The most abundant mRNA transcripts found in a hybridoma cell line did not necessarily encode the antibody chains providing the correct specificity. Consequently, when cloning antibody genes, functional validation of all possible VH and VL combinations is required to identify those with the highest affinity and lowest cross-reactivity. These findings, reflecting the current state of hybridomas used in research, reiterate the importance of using sequence-defined recombinant antibodies for research or diagnostic use.